Identifying and Resolving End of Session Cues in Substance Detection Canine Training - Topoleski, Jan; Schultz, Craig A.; Warren, Wynn G. (Frontiers in Veterinary Science, 2018)
When training and working a substance detection canine, a trained final response should be performed immediately upon recognition of odor (Generally, a 1-3 second window is preferred within our detection practices). Typical canine training places much emphasis on planning and setting up training scenarios to achieve specific objectives but not much consideration is given to how to end a training session. When the canine fails to maintain criteria, trainers are left trying to determine the cause of poor performance. One consideration often overlooked is a phenomenon called End of Session Cueing that may exist in detection training whereby a previously trained canine no longer responds to odor because it has taken on aversive association. This may be due to several factors associated with motivation. The sequence of events at the end of a session can be as equally important to maintain motivation for the task of scent detection in future sessions. This paper will identify and examine multiple factors associated with “End of Session Cues” in working dogs, how they may be responsible for poor final response performance and discuss potential strategies to address them.